Midterm results of Oxford shoulder hemiarthroplasty - Dwyer, Amitabh J (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Hemiarthroplasty of the shoulder is known to provide satisfactory long term results provided concentric reduction can be obtained in a high percentage of patients. Careful soft tissue balancing with appropriate adaptation of version of the component appears to allow good results permitting centering of the arthroplasty without replacement of a glenoid component. MATERIALS AND METHODS: 29 consecutive patients (30 shoulders) who underwent Oxford cementless shoulder hemiarthroplasty between 2004 and 2006 were analyzed. Mean age was 71 years (range 34-91 years, 95% of the confidence interval [CI] of standard deviation [SD] was 10.32-17.58). Mean duration of preoperative symptoms was 42.8 months (range 9-84 months, 95% CI of SD was 17.83-30.11). Patients’ self reported Oxford shoulder score (OSS) was collected prospectively and was used as an assessment tool to measure final outcome. RESULTS: The mean initial OSS was 17.9 (range 7-43, 95% CI of the SD was 7.19-12.13). The score improved by an average of 16.9 points at a mean followup of 5.9 years (range 4.3-7.6 years) to reach mean final OSS of 34.8 (range 13-48, 95% CI of the SD was 9.31-15.73). The improvement of OSS was highly significant with a two tailed P < 0.0001 and 95% CI of this difference was 11.47-22.20. CONCLUSION: This study demonstrates shoulder hemiarthroplasty as reliable procedure for improvement of shoulder function as shown by the patients’ self reported outcome score (OSS) in end stage glenohumeral arthritis with intact or reparable rotator cuff at midterm followup. Our results suggest successful outcome of the Oxford shoulder hemiarthroplasty (Corin, UK) away from its originating center and in hospitals where fewer shoulder replacements are performed.